PEMANFAATAN DESAIN INTERAKSI ANTAR MUKA PENGGUNA DENGAN IMPLEMENTASI MODEL GOMS PADA APLIKASI MOBILE ELMA - Mailia Putri Utami (LPPM Universitas Abdurrab, 2023)
The design of interaction and user interfaces is an element of a digital or computer-based information system. The development of user interface designs can attract users to feel comfortable in conducting online consulting activities. The purpose of this study is to find out the user's needs as a whole in the design of user interactions on the Elma mobile application with the GOMS model. The performance of the GOMS model is a systematic interrelated method that is interrelated with goals, and actions from the operator using the last method and process, namely selection that can reflect the purpose of the user interface design analysis in the application. Applying the GOMS method to the user interface design, it can be said that the application development must pay attention to the user's needs thoroughly, and the ease of user access by the application of the analysis using the